Drug utilization patterns and reported health status in ethnic German migrants (Aussiedler) in Germany: a cross-sectional study - Kostev Karel; Bertsche Thilo; Volodina Anna; Winkler Volker; Haefeli Walter; Becher Heiko (BMC, 2011)
Abstract Background Inadequate utilization of healthcare services by migrant populations is an important public health concern. Inadequate drug consumption and poor compliance to the therapeutic regimen are common manifestations of low health-care seeking behavior present in migrants even in the countries with well-established healthcare systems. There are few studies on the use of medicines among the different groups of migrants in Germany. The objective of this study is to investigate drug consumption patterns of ethnic German migrants (Aussiedler) and their current health status. Methods A cross-sectional study nested into a cohort of 18,621 individuals aged 20-70 years who migrated to Germany from the former Soviet Union between 1990 and 2005 was conducted. Data on consumption of drugs, drug handling, major health risk factors, and one-year disease prevalence were obtained for 114 individuals through a self-administered questionnaire and phone interviews. Results were compared to the data on the German population derived from the Disease Analyzer database and Robert Koch Institute (RKI) annual reports. Direct age standardization, test of differences, Chi-square test, and descriptive statistics were applied as appropriate. For drug classification the Anatomical Therapeutic Chemical (ATC) system was used. Results Of the respondents, 97% reported to have at least one disease within a 12-month period. The one-year prevalence of asthma (6.9%), hypertension (26.7%), chronic bronchitis (8.6%), and diabetes (4.9%) in migrants was similar to the general German population. 51% regularly took either over-the-counter (OTC) medication or prescription medicines. Six ATC groups were analyzed. The highest drug consumption was reported for the ATC cardiovascular (22%), nervous (9%), and muskulo-skeletal system (8%). 30% used OTC medicines obtained in the country of origin. Difficulties with drug handling were rare. Alcohol consumption did not differ from the German population (p = 0.19 males and 0.27 females), however smoking prevalence was lower (p < 0.01) in both sexes. Conclusion Ethnic German migrants seem to differ only slightly from Germans in health status, drug utilization, and disease risk factors, and if so, not in an extreme way. Country of origin remains a source of medicines for a substantial part of migrants. The study is limited by a small sample size and low response rate.